Evaluation of supporting tools for health coaches providing nutrition and exercise coaching to older adults in Singapore - Cao, Yuanyuan (2023)
A rapidly ageing population and multimorbidity are questioning the sustainability of healthcare systems in Singapore, whereby health coaches, who help older adults build and sustain a healthy lifestyle, have become increasingly popular in recent years. Health coaches however face multiple challenges due to caregiver burden. In this study, we designed and evaluated web and mobile applications (“apps”) to support health coaches with scheduling, managing reports, and providing access to resources related to nutrition and exercise for older adults. We examined the acceptance and usability of the apps with health coaches after they completed 8 weekly online health coaching sessions. We found desirable functions included consideration of ethnic diversity in the context of a multi-culture society, potential of providing just- in-time information when they face problems during coaching, and helpful materials and links for health coaches to refer to.